Pathways to career-ending police misconduct: an examination of patterns, timing, and organizational responses to officer malfeasance in the NYPD - White, Michael D. (Criminal justice and behavior, 2013)
Prior research has not sufficiently explained the various pathways that lead to career-ending misconduct among police officers, most notably the timing of misconduct in officers? careers, whether certain factors are related to that timing, and whether the types of misdeeds vary over time. The current study seeks to address these questions through an examination of all officers separated from the New York City Police Department (NYPD) for career-ending misconduct (n = 1,542) from 1975 to 1996 as well as a comparison sample of officers who served honorably during that same time (n = 1,543). The authors adopt a survival perspective using both Cox regression survival analysis and multinomial logistic regression. Results indicate that time to termination is a complex, long-term process with distinct patterns that emerge over police officers' careers. A number of variables were significantly associated with time to termination across officer careers, such as officer race and prior criminal history, while others were significant only at certain career stages. For example, promotion only protected against termination early in an officer's career, while military service was a predictor of misconduct only after 10 years of service. The article highlights the importance of selection screening "out and in" processes, as officers with red flags early in their careers were at greatest risk for dismissal. The results also suggest that police departments themselves play an important role in shaping the patterns and timing of officer misconduct. Moreover, the survival framework provides a foundation for a long-overdue dialogue on good policing.